2020
DOI: 10.1038/s41598-020-59979-0
|View full text |Cite
|
Sign up to set email alerts
|

Auditory-induced body distortions in children and adults

Abstract: Recent studies have shown that body-representations can be altered by dynamic changes in sound. in the so-called "auditory Pinocchio illusion" participants feel their finger to be longer when the action of pulling their finger is paired with a rising pitch. Here, we investigated whether preschool children-an age group in which multisensory body-representations are still fine-tuning-are also sensitive to this illusion. In two studies, sixty adult and sixty child participants heard sounds rising or falling in pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 65 publications
1
18
0
Order By: Relevance
“…When brief sounds rising in pitch are paired and presented synchronously with the action of oneself pulling on one's occluded fingertip can lead to participants feel and estimate their finger to be longer [11] suggesting influences of sound on proprioception. This illusion was replicated both in adults and pre-school children for passive finger pulling [39].…”
Section: Illusory Body Extension Potentially Driven By Sound Influences On Proprioceptionmentioning
confidence: 67%
See 3 more Smart Citations
“…When brief sounds rising in pitch are paired and presented synchronously with the action of oneself pulling on one's occluded fingertip can lead to participants feel and estimate their finger to be longer [11] suggesting influences of sound on proprioception. This illusion was replicated both in adults and pre-school children for passive finger pulling [39].…”
Section: Illusory Body Extension Potentially Driven By Sound Influences On Proprioceptionmentioning
confidence: 67%
“…The first study [11] reported an "auditory Pinocchio"' illusion, in which participants feel and estimate their finger to be longer, elicited by presenting brief sounds rising in pitch with the action of oneself pulling on one's occluded fingertip. This illusion was then replicated [39] both in adults and preschool children, when the experimenter, rather than the participants themselves, pulled the finger of the participant, thus suggesting that the effects of sound on the proprioception of one's fingertip can take place both under passive and active touch conditions. Nevertheless, before the present study, it was unclear whether the effect of sounds changing in pitch on proprioception requires "anchoring" those sounds through tactile cues, as in the case of the "auditory Pinocchio"' illusion.…”
Section: Pitch Change and Bodily Movementmentioning
confidence: 88%
See 2 more Smart Citations
“…Using sound as augmented feedback, in particular movement sonification in contrast to an auditory alarm 2 , has been widely explored in fundamental studies of motor learning, and in specific applications: sports, medicine, pedagogy and performing arts. Movement sonification can be seen as a subfield of sonification research and interactive sound design [31] that explores how sound and music can carry information to users, change perception (from either a first-or third-person perceptive) [11,26,51,55] and more generally increase motivation for certain tasks. From a technological point of view, movement sonification shares methods and technologies with communities 3 focusing on music and performing arts where bodily movements and gestures represent an important theme, but not movement learning [5].…”
Section: Sonification As Augmented Feedbackmentioning
confidence: 99%